(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the current status of postoperative patient handover compliance using the SBAR model by nurses at the Department of Anesthesia and Pain Management, Vinmec Times City International General Hospital, in 2025. Subjects and methods: This is a cross-sectional descriptive study, a total of 400 postoperative cases in the Department of Anesthesia and Pain Management were observed during handovers between shifts or transfers to clinical departments such as Surgery, Obstetrics, Intensive Care, and Orthopedics at Vinmec Times City International General Hospital. Results: Nurses handing over patients verbally according to the SBAR model demonstrated compliance rates of 94% for situation, 91% for background, 91% for assessment, and 91% for recommendation. Based on the checklist, compliance rates were 90% for patient identification, 93% for the patient’s current condition, 93.5% for background information, 93.8% for assessment, and 95.2% for recommendation. Receiving nurses showed even higher verbal compliance rates: 94.8% for situation, 93.8% for background, 92.2% for assessment, and 92.5% for recommendation. Checklist-based compliance among receiving nurses was 95.8% for patient identification, 93.8% for current condition, 94.8% for background, 95% for assessment, and 95% for recommendation. Conclusion: Nurses receiving patient handovers showed higher compliance with the SBAR model than those giving handovers, in both verbal communication and checklist documentation.